Work-Life Balance on Performance with Psychological Well-Being as A Mediating Variable: JEL Clasification: J24, J28, M12, M54, I31 - Siti Aisyah; Okki Trinanda (Journal of Management and Administration Provision, 2026)
This study explores how work-life balance affects performance with psychological well-being as a mediating variable in the context of the Bukittinggi City Tourism Office. The focus of this study is to analyze the relationship between work-life balance, performance, and psychological well-being. Using total sampling techniques, a quantitative research design was applied, and 45 employees participated as respondents. Data were collected through questionnaire distribution, and analysis was performed using the Partial Least Squares (PLS) approach within the Structural Equation Modeling (SEM) framework. The findings indicate that work-life balance has no significant effect on performance. Work-life balance has a positive and significant effect on psychological well-being. Psychological well-being has a positive and significant effect on performance. Work-life balance has a positive and significant effect on performance through psychological well-being.